Dampak Kenakalan Remaja Bahaya Narkoba dan Tawuran - Utami, Ichwani Siti; Pujilestari, Yulita; Putri, Mas Fierna Janvierna Lusie (ABDIMAS Iqtishadia, 2023)
This activity aims to build character and moral education for students with integrity, to increase the social awareness of students of the Teaching and Education Faculty towards students, to provide an understanding of lessons to students at Al-Ihsan Islamic Middle School. This community service method is carried out in the form of counseling by providing education on the importance of the impact of juvenile delinquency on the dangers of drugs and brawls. The media is accompanied by questions and answers and discussion of problems that often occur in the field. The results of community service obtained in this activity are an increase in understanding of the impact of juvenile delinquency on the dangers of drugs and brawls at a young age. They come to understand that what actions can and cannot be done. Therefore, hopefully this service activity can provide benefits for students and it is hoped that it can be carried out in a sustainable manner, especially to have an impact on juvenile delinquency, the dangers of drugs and brawls.